Social Entrepreneurship Model: The Impact of Implementing Corporate Social Responsibility (Case Study of Sido Muncul Partnership Program) - Hani - Sirine; Roos Kities Andadari; Lieli Suharti (International Journal of Business Studies, 2020)
Social entrepreneurship can be integrated into the realm of corporate social responsibility, resulting in a balance between economic value and social value through cooperation and investment. The purpose of this study was to determine the social entrepreneurship model developed by Sido Muncul as an impact of implementing the partnership program with farmers. The research method used is qualitative in which the validity of the data is tested by the triangulation method. Data collection was carried out by interview and observation to Sido Muncul and Sido Muncul's partners. The results of this study indicate that the social entrepreneurship model produced by Sido Muncul's corporate social responsibility program consists of various driving factors, including: the importance of stakeholders, social proactivity, governance, social intrapreneurs, and local wisdom. Social entrepreneurship can be integrated into the realm of corporate social responsibility, resulting in a balance between economic value and social value through cooperation and investment. The purpose of this study was to determine the social entrepreneurship model developed by Sido Muncul as an impact of implementing the partnership program with farmers. The research method used is qualitative in which the validity of the data is tested by the triangulation method. Data collection was carried out by interview and observation to Sido Muncul and Sido Muncul's partners. The results of this study indicate that the social entrepreneurship model produced by Sido Muncul's corporate social responsibility program consists of various driving factors, including: the importance of stakeholders, social proactivity, governance, social intrapreneurs, and local wisdom.